Nanoporous electroporation needle for localized intracellular delivery in deep tissues - Gyeong Won Lee; Byeongyeon Kim; Tae Wook Lee; Sang‐Gu Yim; Ajeesh Chandrasekharan; Hyewon Kim; Sungyoung Choi; Seung Yun Yang (Wiley, 2023)
Abstract The exogenous control of intracellular drug delivery has been shown to improve the overall efficacy of therapies by reducing nonspecific off‐target toxicity. However, achieving a precise on‐demand dosage of a drug in deep tissues with minimal damage is still a challenge. In this study, we report an electric‐pulse‐driven nanopore‐electroporation (nEP) system for the localized intracellular delivery of a model agent in deep tissues. Compared with conventional bulk electroporation, in vitro nEP achieved better transfection efficiency (>60%) with a high cell recovery rate (>95%) under a nontoxic low electroporation condition (40 V). Furthermore, in vivo nEP using a nanopore needle electrode with a side drug‐releasing compartment offered better control over the dosage release, time, and location of propidium iodide, which was used as a model agent for intracellular delivery. In a pilot study using experimental animals, the nEP system exhibited two times higher transfection efficiency of propidium iodide in the thigh muscle tissue, while minimizing tissue damage (<20%) compared to that of bulk electroporation. This tissue‐penetrating nEP platform can provide localized, safe, and effective intracellular delivery of diverse therapeutics into deep tissues in a controlled manner.